Pembelajaran Ansambel Musik Sejenis Pada Siswa Kelas VII.1 Di SMP N 29 Padang - Putry Vadillah Sukma; Harisnal Hadi (Universitas Palangka Raya, 2023)
This study aims to describe the implementation of similar music ensembles in grade VII.1 students at SMP Negeri 29 Padang. This type of research is qualitative research with a descriptive approach. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The data in this study used primary data and secondary data. The steps of analyzing the data are collecting data, identifying the data, clarifying the data, describing the data and inferring the data. The results showed that cultural arts learning in class VII.1 at SMP N 29 Padang used the 2013 curriculum syllabus by applying the 2013 curriculum pattern method, namely, student-centered learning patterns, active patterns, group patterns, multimedia-based learning patterns, and plural learning patterns. Cultural arts learning which was supposed to be 3 meetings to 2 meetings made it a little difficult for students to face the exam of similar musical ensembles. The lack of facilities and infrastructure does not hinder teachers in developing their creativity in order to continue to achieve learning objectives